Short-term effectiveness of bi-phase oscillatory waves versus hyperthermia for isolated long head biceps tendinopathy - Oliva, Francesco (CIC Edizioni Internazionali, 2012)
INTRODUCTION: Long head biceps (LHB) tendinopathy is a common cause of anterior shoulder pain. Isolated LHB pathology is most common among younger people who practise overhead sports. The authors conducted a short-term prospective randomised study to test the effectiveness of two different methods for the treatment of isolated LHB tendinopathy: biphasic oscillatory waves and hyperthermia. STUDY DESIGN: The study is a prospective randomised study (Level II). MATERIAL AND METHODS: The authors identified 20 patients who had clinical and ultrasound (US) evidence of LHB tendinopathy. No patient was a high-level athlete. The patients were randomly assigned to two groups. Group A (10 patients) was treated with bi-phasic oscillatory waves, while Group B received hyperthermia. During the treatment period, no other electromedical therapy, injections with corticosteroids, oral analgesics or nonsteroidal anti-inflammatory drugs were allowed. All the patients were assessed at baseline (T0), immediately after the end of the treatment period (T1) and 6 months after the end of treatment (T2) using a visual analogic scale (VAS) and Constant-Murley Score (CMS). Furthermore, all patients underwent US examinations at T0 and at T1. All the US examinations were performed by the same radiologist. RESULTS: The VAS scores showed a highly statistically significant reduction of pain at T1 both in Group A (65%; p=0,004) and in Group B (50%; p=0,0002). The CMS also showed a statistically significant improvement between the pre-intervention, the post-treatment and the short-term follow-up in both groups. In addition, the peritendinous fluid evident on US examination at T0 was no longer present in all cases at T1. CONCLUSION: These findings suggest that both bi-phasic oscillatory waves and hyperthermia are able to relieve pain in patients with isolated LHB tendinopathy. This is a Class II level of evidence.